Distribution Pattern of Cadmium in the Profile of Shallow Fissure Soil and Its Influencing Factors in Karst Areas with High Geological Background - FAN Pingping; CHEN Jia; ZHANG Feng; NIU Yong; FANG Nufang; WU Zeyan; CAI Huayin (Shuitu Baochi Xuebao)
[Objective] To study the vertical distribution pattern of cadmium (Cd) in shallow karst fissure soil, analyze the impacts of various factors on the distribution of Cd in fissures, and provide a scientific basis for future research on the distribution pattern of Cd in underground fissure soil and the prevention and control of Cd pollution. [Methods] Taking the small watershed of Baobao Mountain in Weining County, a region with a typical high geological background in the northwest of Guizhou, as the research object, the total Cd concentration and speciation of Cd in shallow fissure soil, along with five soil property indicators such as pH value, organic matter content, cation exchange capacity (CEC), particle size, and aggregate were systematically analyzed. The distribution pattern of Cd and its influencing factors were examined using one-way ANOVA and correlation analysis. [Results] (1) The physical and chemical properties of the fissure soil significantly affected the distribution of Cd. (2) The average pH value of the fissure soil was 6.70. The average Cd concentration was 2.99 mg/kg, the concentration was high at 0—20 cm and gradually decreased with increasing soil depth, and Cd was predominantly in the reducible form. (3) Total Cd concentration was mainly influenced by soil pH, CEC, clay, silt, and water-stable aggregates, with CEC being the primary controlling factor for the vertical distribution of Cd. (4) The distribution of Cd speciation was controlled by different factors, depending on the form of Cd, with the weak acid-extractable form primarily influenced by organic matter, the reducible form mainly influenced by CEC, the oxidizable form mainly influenced by CEC, clay, and silt, and the residual form mainly influenced by silt content. (5) There was a significant difference in Cd concentration between the soils of funnel-shaped and trapezoidal fissure profiles and the rectangular fissure profile. [Conclusion] The vertical distribution pattern of Cd in fissure soil is jointly influenced by soil physicochemical properties and fissure morphology, with rectangular fissures being more conducive to the accumulation of Cd.